2023
DOI: 10.1021/acssuschemeng.3c02036
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Catalytic Depolymerization for Phenolic Monomers: Boosting the Selective Cleavage of β-O-4 Bonds of Lignin by Mo═O and Al(IV)–O–BO2 Interfacial Sites in B–Mo/Sepiolite

Abstract: Selective breaking of β-O-4 bonds is a challenge for lignin depolymerization. Herein, boron (B) was utilized to construct superficial MoO and subsurface Al(IV)–O–BO2 interfacial sites of Mo/sepiolite (SEP), which acted as Lewis acid sites to promote β-O-4 bond cleavage of lignin. Characterizations and density functional theory (DFT) calculations showed that B could interact with the quadridentate Al(IV) atoms of SEP to generate Al(IV)–O–BO2 and did not affect the incipient MoO of Mo/SEP. The experimental res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…[91,127] Chen et al investigated the cleavage of a βÀ O-4 model compound catalyzed by a boron-doped Mo/SEP in supercritical ethanol. [128] The integration of boron into the catalyst modulated the electron distribution over the active metallic sites, thus enhancing electron transfer between the substrate and the metal and improving the adsorption of the substrate. The computational analysis clarified the kinetics and mechanisms influencing the model compound's conversion process facilitated by the catalyst (Figure 3e).…”
Section: Hydrogenolysis Of Dimer Model Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…[91,127] Chen et al investigated the cleavage of a βÀ O-4 model compound catalyzed by a boron-doped Mo/SEP in supercritical ethanol. [128] The integration of boron into the catalyst modulated the electron distribution over the active metallic sites, thus enhancing electron transfer between the substrate and the metal and improving the adsorption of the substrate. The computational analysis clarified the kinetics and mechanisms influencing the model compound's conversion process facilitated by the catalyst (Figure 3e).…”
Section: Hydrogenolysis Of Dimer Model Compoundsmentioning
confidence: 99%
“…Adapted with permission from ref. [128] Copyright 2023, American Chemical Society. hydroxyl group were not adequate for the complete dissociation of the ether bond, resulting in a partially degraded intermediate marked by a modified γÀ OH group.…”
Section: Hydrogenolysis Of Dimer Model Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the lignin content of Douglas fir (Table 1), a softwood [39], was higher than that of poplar, its bio-oil contained the lowest level of lignin-derived compounds (42.29%) compared to that of eucalyptus (60.62%) and poplar (67.04%). The discrepancy in the concentration of the lignin-derived compounds in the bio-oil and the lignin content of the respective biomass can be explained by the number of easily breakable β-O-4 linkages present in the biomass [40,41]. For instance, for the same mass of Douglas fir and poplar, Yoo et al [31] found 87 β-O-4 linkages in poplar, which was greater than the number of β-O-4 bonds present in Douglas fir (total linkages = 68).…”
Section: Gas Chromatography-mass Spectroscopy (Gc-ms) Analysismentioning
confidence: 99%
“…1) Most literature research dedicated to lignin depolymerization, aims to effectively cleave these ether bonds yielding various aromatic compounds. 2–6 These compounds can then undergo hydrodeoxygenation to obtain a high-quality bio-oil. 7…”
Section: Introductionmentioning
confidence: 99%